Chile: Acceptability of a Training Program for Depression Management in Primary Care - Marín, Rigoberto (Front Psychol, 2016)
Background: In Chile, there are inconsistencies in the management of depression in primary care settings, and the National Depression Program, currently in effect, was implemented without a standardized training program. The objective of this study is to evaluate the acceptability of a training program on the management of depression for primary care health teams. Methods: The study was a randomized controlled trial, and two primary centers from the Metropolitan Region of Santiago were randomly selected to carry out the intervention training program. Pre-post surveys were applied, to evaluate expectations and satisfaction with the intervention, respectively. Descriptive and content analysis was carried out. Result: The sample consisted of 41 health professionals, 56.1% of who reported that their expectations for the intervention were met. All of the training activities were evaluated with scores higher than 6.4 (on a 1–7 scale). The trainers, the methodology, and the learning environment were considered strengths and facilitators of the program, while the limited duration of the training, the logistical problems faced during part of the program, and the lack of educational material were viewed as weaknesses. Conclusion: The intervention was well accepted by primary health care teams. However, the clinical impact in patients still has to be evaluated.